2007
DOI: 10.5194/angeo-25-1113-2007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of radio frequency signals by ULF waves

Abstract: Abstract. The ionospheric plasma is continually perturbed by ultra-low frequency (ULF; 1-100 mHz) plasma waves that are incident from the magnetosphere. In this paper we present a combined experimental and modeling study of the variation in radio frequency of signals propagating in the ionosphere due to the interaction of ULF wave energy with the ionospheric plasma. Modeling the interaction shows that the magnitude of the ULF wave electric field, e, and the geomagnetic field, B 0 , giving an e×B 0 drift, is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…Signatures of ULF waves have been seen in both the ionosphere and ground scatter returns (Walker et al, 1979;Fenrich et al, 1995;Yeoman et al, 2000;Ponomarenko et al, 2001;Baddeley et al, 2002;Ponomarenko et al, 2005;Fenrich et al, 2006;Waters et al, 2007). The radars can detect ULF signatures when the spatial scale prevents the signal appearing at the ground (Yeoman et al, 2000;Yeoman and Wright, 2001;Baddeley et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signatures of ULF waves have been seen in both the ionosphere and ground scatter returns (Walker et al, 1979;Fenrich et al, 1995;Yeoman et al, 2000;Ponomarenko et al, 2001;Baddeley et al, 2002;Ponomarenko et al, 2005;Fenrich et al, 2006;Waters et al, 2007). The radars can detect ULF signatures when the spatial scale prevents the signal appearing at the ground (Yeoman et al, 2000;Yeoman and Wright, 2001;Baddeley et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, to obtain more complete information, ULF data are required over a spatial region in the ionosphere. A few spatial measurements of ULF waves in the ionosphere have been obtained using Dopppler sounding techniques (Yeoman et al, 2000;Baddeley et al, 2005;Waters et al, 2007). ULF scale sizes down to 50 km have been observed for latitudes near L=6 (Baddeley et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The coupled MHD equations describing these modes in an anisotropic collisional plasma can be found in Waters et al (2007) and Fedorov et al (2016). The vertical profile of local of the ionospheric parameters (conductivity tensor, Alfven velocity, electron mobility tensor, etc.)…”
Section: Possible Mechanisms Of Tec Modulation By Mhd Wavesmentioning
confidence: 99%
“…Low-Earth orbit satellites can detect a high-frequency part only of ULF spectrum (Pc1-3 waves). Ionospheric signatures of long-period ULF waves (Pc4-5, Pi2-3) can be detected by modern HF radio sounding techniques: Doppler sounders (Menk et al 2007;Waters et al 2007;Pilipenko et al 2013) and SuperDARN HF radars (Lester et al 2000;Ponomarenko et al 2001;Teramoto et al 2014). The ever-growing array of global satellite navigation systems (GPS, GLONASS, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms also contributed. Waters et al (2007) have considered oblique propagation and have shown that the dominant mechanism for pulsations is the vertical E × B drift due to the pulsation field, which affects the path through the SP mechanism. A limitation of such observations is that the perturbation occurs in the ionosphere where the pulsation is located, while the radar measured the range of the ground.…”
Section: Determination Of Resonance Nature Of Eventsmentioning
confidence: 99%